Applying problem-based learning in Civic education podcasts boosts critical thinking and student outcomes at Community Learning Center (CLC) - Al’fi Nasikin; Sri Untari; Edi Suhartono (Inovasi Kurikulum, 2025)
This classroom action research aimed to enhance Civics learning outcomes for CLC Pasir Putih class IX students of SMP Keningau Bingkor in Sabah, Malaysia, using the Problem-Based Learning (PBL) method supported by podcast media. During the 2023/2024 academic year, the study involved 21 students and addressed unsatisfactory learning conditions while improving instructional quality. In Cycle I, only 12 students met the minimum completion criteria (KKM) of 75, with nine falling short. By Cycle II, significant improvement was observed: 19 students achieved the KKM, and the class average rose to 80. This exceeded the school's classical target completion. The podcast-based PBL model fostered interactive and engaging lessons, countering the monotony of conventional methods. Students reported increased motivation as podcasts made materials more accessible and flexible for repeated learning. The innovative approach allowed them to learn anytime, anywhere, enhancing comprehension. Overall, students expressed enthusiasm for continuing this method, citing its effectiveness and enjoyment. Their positive responses underscored how combining PBL with podcast media improved academic performance and created a dynamic, student-centered learning environment.   Abstrak Penelitian tindakan kelas ini bertujuan untuk meningkatkan hasil belajar Pendidikan Kewarganegaraan peserta didik Kelas IX CLC Pasir Putih SMP Keningau Bingkor di Sabah, Malaysia, menggunakan metode Problem-Based Learning (PBL) berbasis podcast. Penelitian dilaksanakan pada tahun akademik 2023/2024 dengan melibatkan 21 peserta didik, dengan tujuan memperbaiki kondisi pembelajaran yang kurang memuaskan dan meningkatkan kualitas pengajaran. Pada Siklus I, hanya 12 peserta didik yang mencapai Kriteria Ketuntasan Minimal (KKM) yaitu 75, sementara 9 peserta didik belum mencapainya. Pada Siklus II, terjadi peningkatan signifikan: 19 peserta didik berhasil mencapai KKM, dengan rata-rata nilai kelas mencapai 80, melebihi target klasikal sekolah. Model PBL berbasis podcast menciptakan pembelajaran interaktif dan menarik, menghilangkan kebosanan metode konvensional. Peserta didik melaporkan motivasi belajar meningkat karena materi disajikan secara menarik dan fleksibel. Podcast memungkinkan peserta didik belajar kapan saja dan di mana saja, sehingga mereka dapat mengulang materi sesuai kebutuhan. Secara keseluruhan, peserta didik antusias melanjutkan metode ini karena dinilai efektif dan menyenangkan. Tanggapan positif peserta didik menunjukkan bahwa kombinasi PBL dan podcast tidak hanya meningkatkan hasil akademik tetapi juga menciptakan lingkungan belajar yang dinamis dan berpusat pada peserta didik. Kata Kunci: hasil belajar; podcast; problem-based learning